The Role Of Games Learning Media In Increasing Digital Literacy Of Preschool Students - Kasmiati Kasmiati (Jurnal Ilmu Sosial Mamangan, 2024)
Matter This important to align and stabilize this problem to create learning conditions that is right on target and achieves development optimally from an early age. Apart from learning and learning at school, teachers must use source or tool help promotion learning and effective. Position media or tool help hold role important Because cansupport the student learning process. The use of media or tools can create material learning from abstract become concrete, make atmosphere Study Which less comfortable becomes attractive. One of the interesting learning media is cartoon. Planning environment Study games should create process interesting, interactive and entertaining learning and increasing motivation learning in early childhood. This research was conducted through Classroom Action Research (PTK), which includes four steps from the main concepts of Classroom Action Research, that is: Plan And carry out action, do observation and reflection. Based on the results and discussion, it can be concluded that the use of games can increase student motivation in the aspect of observing all presentations of material delivered by the teacher in teaching. The use of games can increase student motivation in the aspect of trying to do tasks correctly in completing tasks. The use of games can increase student motivation in the aspect of wanting to know asking looking for answers.